2020
DOI: 10.1038/s41598-020-67506-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative SPECT/CT for differentiating between enchondroma and grade I chondrosarcoma

Abstract: Although differentiation between central chondroid tumors is important, their parallelism makes it a diagnostic conundrum for clinicians and radiologists. The objective of this study was to evaluate the efficiency of quantitative single photon emission computed tomography (SPECT)/computed tomography (CT) in differentiating grade I chondrosarcomas from enchondromas. We reviewed SPECT/CT images of patients with enchondromas and grade I chondrosarcomas arising in the long bones. Volume, mean standardized uptake v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The bone scintigraphy is based on the assessment of technetium 99m-methyl diphosphonate (Tc-99m MDP), thallium-201, or technetium-99m dimercaptosuccinic acid Tc-99m DMSA (V) [ 118 ]. The majority of CHSs are characterized by enhanced radionuclide uptake (compared to the anterior iliac crest) at bone scintigraphy [ 107 , 119 ]. A recent study demonstrated that elevated thallium-201 uptake was associated with almost eight times greater odds of grade 1 CHSs than enchondromas and elevated Tc-99m DMSA (V) uptake—nearly five times greater odds for CHS [ 120 ].…”
Section: Imaging Methods In Chondrosarcomamentioning
confidence: 99%
See 2 more Smart Citations
“…The bone scintigraphy is based on the assessment of technetium 99m-methyl diphosphonate (Tc-99m MDP), thallium-201, or technetium-99m dimercaptosuccinic acid Tc-99m DMSA (V) [ 118 ]. The majority of CHSs are characterized by enhanced radionuclide uptake (compared to the anterior iliac crest) at bone scintigraphy [ 107 , 119 ]. A recent study demonstrated that elevated thallium-201 uptake was associated with almost eight times greater odds of grade 1 CHSs than enchondromas and elevated Tc-99m DMSA (V) uptake—nearly five times greater odds for CHS [ 120 ].…”
Section: Imaging Methods In Chondrosarcomamentioning
confidence: 99%
“…A recent study demonstrated that elevated thallium-201 uptake was associated with almost eight times greater odds of grade 1 CHSs than enchondromas and elevated Tc-99m DMSA (V) uptake—nearly five times greater odds for CHS [ 120 ]. However, a limitation of bone scintigraphy is a subjective visual evaluation of the images and resulting inter-observer variability [ 119 ].…”
Section: Imaging Methods In Chondrosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the usefulness of radiological findings in X-ray, CT, MRI, and nuclear medicine [ 9 , 14 , 15 , 16 , 20 , 28 , 29 , 30 , 31 ]. Although these radiological examinations are commonly used for making this distinction [ 15 , 32 ], there is no standard evaluation method of the radiological examinations.…”
Section: Discussionmentioning
confidence: 99%
“…For visual analysis, ordered-subset expectation maximization (OSEM) with 2 iterations, and 10 subsets was used for image reconstruction with Butterworth post-filtering (frequency of 0.60 cycles/cm, power 10), and the images were displayed as a 128 × 128 matrix with a section thickness of 3.88 mm. For quantitative analysis, the images were reconstructed using OSEM with 4 iterations and 10 subsets without post-filtering, which is a proven optimized reconstruction method for quantification [ 13 15 ].…”
Section: Methodsmentioning
confidence: 99%